Penerapan Konsistensi Pola Asuh Orang Tua Terhadap Perilaku Anak Usia Dini - Azizah, Annafi' Nurul 'Ilmi; Devina Putri Kurniasari; Zahwa Risma Rizqiana; Tsaltsa Amaliah Nur Hafidah; Sintiyasari; Ida Sofiyani (Zuriah Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of this study was to examine the relationship between positive early childhood behaviors and consistent parenting. The background of this study centers on how important parenting is in shaping a child's personality and character, especially during the critical developmental period at the age of 5-6 years. This research used descriptive qualitative methodology, collecting data through documentation, in-depth interviews and observation. Parents with young children were the research subjects, with an emphasis on the continuous use of democratic parenting. Findings showed that practicing effective parenting continuously had positive effects on children's behavior, including the development of social skills, discipline, empathy and a growing sense of responsibility. Key contributing elements are active parental participation, open communication and modeling. On the other hand, inconsistent parenting can cause children to behave negatively and aimlessly. The findings of this study confirm that excellent early childhood character and behavior development is greatly aided by consistent parenting.